Digital Transformation in Healthcare 5.0 : Volume 1: IoT, AI and Digital Twin - Agarwal, Vedik; Akın İnsel, Mert; Albayrak, Inci; Ali, Sajid; Chaudhary, Sachin; Gonce Kocken, Hale; Jayashree, J.; Jitendra Chandnani, Chirag; Kadry, Seifedine; Kalinaki, Kassim; Karakuş, Selcan; Kaur Thethi, Sukhmani; et al. (Smart Computing Applications ,, 2024)
"Digital Transformation in Healthcare 5.0: IoT, AI, and Digital Twin" provides a comprehensive overview of the integration of cutting-edge technology with healthcare, from the Fourth Industrial Revolution (4IR) to the introduction of IoT, AI, and Digital Twin technologies. This in-depth discussion of the digital revolution expanding the healthcare industry covers a wide range of topics, including digital disruption in healthcare delivery, the impact of 4IR and Health 4.0, e-health services and applications, virtual reality's impact on accessible healthcare delivery, digital twins and dietary health technologies, big data analytics in healthcare systems, machine learning models for cost-effective healthcare delivery systems, affordable healthcare with machine learning, enhanced biomedical signal processing with machine learning, and data-driven AI for information retrieval of biomedical images.